2013
DOI: 10.1080/0305215x.2013.812726
|View full text |Cite
|
Sign up to set email alerts
|

Efficient PCA-driven EAs and metamodel-assisted EAs, with applications in turbomachinery

Abstract: This article presents methods to enhance the efficiency of Evolutionary Algorithms (EAs), particularly those assisted by surrogate evaluation models or metamodels. The gain in efficiency becomes important in applications related to industrial optimization problems with a great number of design variables. The development is based on the principal components analysis of the elite members of the evolving EA population, the outcome of which is used to guide the application of evolution operators and/or train depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…There have been other methods that use principal components for highdimensional surrogate-based optimization. For example, Kyriacou et al (2014) used principal components analysis (PCA) in a metamodel-assisted evolutionary algorithm to guide the application of evolution operators and the training of the metamodel. Moreover, Chen et al (2015) used Karhunen-Loève expansion, which is similar to PCA, to reduce design-space dimensionality in metamodel-based shape optimization.…”
Section: Introductionmentioning
confidence: 99%
“…There have been other methods that use principal components for highdimensional surrogate-based optimization. For example, Kyriacou et al (2014) used principal components analysis (PCA) in a metamodel-assisted evolutionary algorithm to guide the application of evolution operators and the training of the metamodel. Moreover, Chen et al (2015) used Karhunen-Loève expansion, which is similar to PCA, to reduce design-space dimensionality in metamodel-based shape optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In some aerodynamic designs, the application of PCA is mainly on the data processing, e.g., classifier. Some examples can be seen in reduced-order models for simulations balancing computation cost and flowfield accuracy in numerous fields [22,[53][54][55][56].…”
Section: Principal Component Analysis As Data Manipulatormentioning
confidence: 99%
“…In the same context, Kyriacou et al. 26 showed that for certain applications, omitting the PCs with the largest variances leads to improved modelling.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Jolliffe, 24 however, states and proves that this strategy does not apply to all cases and results strongly depend on the specific application. In the same context, Kyriacou et al 26 showed that for certain applications, omitting the PCs with the largest variances leads to improved modelling.…”
Section: Principal Component Analysismentioning
confidence: 99%